Prevalence and Age Structure of Polypharmacy in Poland: Results of the Analysis of the National Real-World Database of 38 Million Citizens - Kardas, Przemysław; Urbański, Filip; Lichwierowicz, Aneta; Chudzyńska, Ewa; Kardas, Grzegorz; Czech, Marcin (Frontiers in Pharmacology, 2021)
Introduction: Polypharmacy is a risk factor for adverse health outcomes, higher use of medical services and additional costs. The problem has gained attention as a consequence of aging and related multimorbidity. Therefore, there is an urgent need to adopt effective interventions aimed at reducing its burden. In order to achieve this, in-depth understanding of the prevalence of polypharmacy is required. Of particular interest is, however, assessing prevalence of polypharmacy in various age groups, to reach the right target for these interventions. So far, only limited data on polypharmacy among non-elderly individuals have been available. Aim of study: To assess overall prevalence of polypharmacy in Poland as well as its distribution in various age groups using real-world data. Methodology: A retrospective analysis of complete dispensation data of national payer organisation for the years 2018-2019. The analysed dataset included data on dispensation of reimbursed drugs, and exclusively for 2019, also non-reimbursed drugs. Polypharmacy was defined as dispensation of ≥5 prescription medications within six months. Results: In the analysed national cohort of 38 million Polish citizens, the prevalence of polypharmacy was found to be 11.7% in 2018 and 11.6% in 2019. With age, the prevalence of polypharmacy increased, reaching the value of 56.0% in those aged 80+ in 2018, and 55.0% in 2019. Altogether, among those aged 65+, the polypharmacy was present in 43.1% in 2018, and 42.1% in 2019. In the youngest group of citizens, i.e. among those aged below 20 years, polypharmacy was found in 0.9%, and 0.8% in 2018 and 2019, respectively. Prevalence of polypharmacy, calculated for 2019 according to dispensation of five or more reimbursed and non-reimbursed drugs for the whole Polish population, was 21.8% for January-June, and 22.4% for July-December 2019. Among those aged 65+, the relevant numbers were 62.3%, and 62.9%, respectively. Conclusions: This study, being the first nationwide assessment of polypharmacy in Poland, confirmed its high prevalence. We found polypharmacy present in over one fifth of Polish society. Peaking in the elderly, polypharmacy occurred in each age group. These results lay the foundations for future interventions focused on reducing the scope of this problem in Poland.